The resection of extraosseous osteosarcoma was accompanied by the occurrence of pulmonary metastasis and distal metastasis at the primary site: a case report - Han Liu; Leilei Tian; Jianhua Mu; Xuanhong He; Li Zhuangzhuang; Taojun Gong; Jingjing Wang; Li Min; Minxun Lu; Chongqi Tu (Frontiers in Oncology)
BackgroundExtraskeletal osteosarcoma (ESOS) is a rare and aggressive malignancy, comprising approximately 1% of all soft tissue sarcomas and 4.3% of all osteosarcomas. It predominantly affects individuals between the ages of 48 and 60, with a slightly higher incidence observed in males compared to females. The clinical diagnosis of ESOS poses a significant challenge due to its atypical presentation and overlap with other soft tissue neoplasms. Despite advances in diagnostic imaging and histopathological techniques, there is currently no consensus on the optimal treatment strategy.Case presentationWe report a case of a 64-year-old Chinese woman with ESOS of the left knee for 7 years, who experienced multiple recurrences after surgical resection, accompanied by systemic multiple soft tissue metastases and lung metastases. Initially, the patient found a painless mass in the left knee, which was diagnosed as a benign soft tissue mass at a local hospital and surgically removed. However, two years after the surgery, a mass recurred around the left knee and was larger than before, prompting the patient to seek treatment at our department. The patient underwent standard surgical treatment in our department, and postoperative histopathology, genetic testing, and immunohistochemical examination all confirmed the diagnosis of ESOS. Over the course of 5 years, the patient experienced multiple recurrences, and we attempted surgical treatment combined with chemotherapy and targeted therapy. Ultimately, due to multiple tumor ruptures in the left lower limb, severe pain, and sleep disorders, the patient decided to undergo left hip disarticulation surgery.ConclusionThe diagnosis and treatment of ESOS are challenging and require multimodal examination, including histological and immunohistochemical analysis. ESOS is rare, especially when it metastasizes to the distal soft tissues of the primary lesion site, which may portend a poorer clinical outcome compared to pure pulmonary metastasis. Despite current therapeutic interventions, this case still emphasizes its aggressiveness and poor prognosis.